TRANSFORMASI KURIKULUM DAN INOVASI PEMBELAJARAN UNTUK MEMPERSIAPKAN MAHASISWA MENGHADAPI ABAD 21 - Ali Ramatni; Pahmi; Dony Kristian; A. Darussalam; Singgih Prastawa; Muhammad Rifai (EDU RESEARCH, 2024)
This article discusses the importance of curriculum transformation and learning innovation in higher education to prepare students to face the challenges of the 21st century. In the era of globalisation and rapid technological development, students need to be equipped with 21st century skills such as critical thinking, creativity, collaboration, and effective communication. Curriculum transformation includes interdisciplinary integration, strengthening project-based learning, and developing soft competencies. Meanwhile, learning innovation can be done through the use of digital technology, problem-oriented learning, and the application of student-centred learning approaches. This article emphasises that a paradigm shift in higher education is needed so that graduates can adapt and contribute optimally in the 21st century era. Effective implementation of curriculum transformation and learning innovation will prepare students to become graduates who are superior, innovative, and able to compete at the global level.